Synthesis and Anticancer Activity of 2’-hydroxy-2-bromo-4,5-dimetoxychalcone Against Breast Cancer (MCF-7) Cell Line - Retno Aliyatul Fikroh; Sabirin Matsjeh; Chairil Anwar (Universitas Jenderal Soedirman, 2020)
Breast cancer is one of cancer causes of death in woman. Chemotherapy is one cancer treatment give toxic effects on normal cells. Alternative of cancer treatment by using flavonoid derivative have potent anticancer to reduce side effects of cancer. Chalcone is family of flavonoid that have biological activity. Chalcone derivatives have potential compound as anticancer agent. Chalcone with the presence halogen, metoxy group in ring B is know to inhibit cancer cells. The aims of this research were to synthesize chalcone derivate with bromo, methoxy, and hyroxy group in ring chalcone and to determine the anticancer activity of chalcone derivative. The chalcone derivative was synthesized from 2-hydroxyacetophenone with 2-bromo-4,5-dimethoxybenzaldehyde by Claisen-Schmidt reaction. In vitro cytotoxicity against breast cancer cell was tested by MTT assay method. The compound of 2’-hydroxy-2-bromo-4,5-dimethoxychalcone was yield in 78% as yellow solid. The IC50 of 2’-hydroxy-2-bromo-4,5-dimethoxychalcone was 42,19 µg/mL as a moderate activity to inhibiting breast cancer cell line. Cytotoxity of docorubicin againts breast cancer cell line more active than 2’-hydroxy-2-bromo-4,5-dimethoxychalcone with IC50 10,61 µg/mL. Doxorubicin as drug standar had better anticancer activity than 2’-hydroxy-2-bromo-4,5-dimethoxychalcone. Based on the IC50 value, the compound 2’-hydroxy-2-bromo-4,5-dimethoxychalcone has a moderate activity towards breast cancer cell lines. This study can recommend as candidate for anticancer againts breast cancer cell lines.